2017
DOI: 10.1186/s13071-017-2523-8
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance-associated protein 4 is a bile transporter of Clonorchis sinensis simulated by in silico docking

Abstract: BackgroundMultidrug resistance-associated protein 4 (MRP4) is a member of the C subfamily of the ABC family of ATP-binding cassette (ABC) transporters. MRP4 regulates ATP-dependent efflux of various organic anionic substrates and bile acids out of cells. Since Clonorchis sinensis lives in host’s bile duct, accumulation of bile juice can be toxic to the worm’s tissues and cells. Therefore, C. sinensis needs bile transporters to reduce accumulation of bile acids within its body.ResultsWe cloned MRP4 (CsMRP4) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…To obtain reliable homologous models of parasites, combined approach of 3D modeling methods and re nement were employed [17,18,19,58,59,60]. All predicted 3D models of IF-CsSBAT were evaluated using homology modeling programs such as Swiss-Model [28], IntFOLD [29], Phyre2 [30], RaptorX [31], and HHpred [32], and threading-based modeling program such as I-TASSER [33] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain reliable homologous models of parasites, combined approach of 3D modeling methods and re nement were employed [17,18,19,58,59,60]. All predicted 3D models of IF-CsSBAT were evaluated using homology modeling programs such as Swiss-Model [28], IntFOLD [29], Phyre2 [30], RaptorX [31], and HHpred [32], and threading-based modeling program such as I-TASSER [33] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…iii) The compound to be identi ed as a competitive inhibitor of taurocholate should reveal higher a nity than natural bile acids, ranging from −6.2 to −9.0 kcal/mol [25]. Theoretically, the binding energies of several bile acids against IF-CsSBAT and OF-CsSBAT conformations ranged from −6.1 to −8.7 kcal/mol (Table 3) [19]; however, those of HsASBT (CsSBAT homolog) were −9.0 kcal/mol and −9.2 kcal/mol against natural bile acids and PATD (lead compound blocking HsASBT), respectively [25]. Thus, a cut-off value was set at −9.2 kcal/mol since the present study aimed to explore the most probable inhibitor candidates binding to CsSBAT.…”
Section: Putative Inhibitors Targeting At Bile Acid-binding Pocketmentioning
confidence: 99%
“…The recombinant CsAg17 partial protein was dialyzed against 1× PBS and subjected to 12% gradient gel electrophoresis. Polyclonal antibodies were produced by immunizing BALB/c mice with the recombinant CsAg17 partial protein and used for immunohistochemical staining of C. sinensis adults [17].…”
Section: Production Of Recombinant Csag17 B Cell Epitope Proteinmentioning
confidence: 99%
“…iii) The compound to be identi ed as a competitive inhibitor of taurocholate should reveal higher a nity than natural bile acids, ranging from − 6.2 to − 9.0 kcal/mol [25]. Theoretically, the binding energies of several bile acids against IF-CsSBAT and OF-CsSBAT conformations ranged from − 6.1 to − 8.7 kcal/mol (Table 3) [19]; however, those of HsASBT (CsSBAT homolog) were − 9.0 kcal/mol and − 9.2 kcal/mol against natural bile acids and poly(acrylic acid)-tetraDOCA conjugate (PATD; lead compound blocking HsASBT), respectively [25]. Thus, a cut-off value was set at − 9.2 kcal/mol since the present study aimed to explore the most probable inhibitor candidates binding to CsSBAT.…”
Section: Putative Inhibitors Targeting At Bile Acid-binding Pocketmentioning
confidence: 99%
“…Notably, bile acids trigger physiological stimuli; however, these metabolites can have detrimental effects on C. sinensis survival, as evidence suggests that the accumulated bile acids can cause toxicity to the worm's tissues and cells [18,19]. Recent studies reported that bile components can be toxic or detrimental to C. sinensis survival [10,20,21].…”
Section: Introductionmentioning
confidence: 99%